ROMANIA’S DIPLOMATIC EFFORTS TOWARD SOME SOCIALIST COUNTRIES IN SEARCH OF A PEACEFUL SETTLEMENT-ENDED WAR IN VIETNAM - Le Xuan Thong; Nguyen The Ha (Romanian Journal of Historical Studies, 2023)
The article focuses on Romania's efforts towards socialist countries to find a peaceful solution to end the Vietnam War. To research the contents of the article, the author uses two main research methods of Historical Science (historical method and logical method). In particular, the historical method helps the author "reconstruct" the panorama of Romania's diplomatic activities towards Socialist countries on finding a peaceful solution to end the war that took place from 1965 to 1973, on the basis of exploiting different historical sources. The logical method helps the author make appropriate and persuasive comments and assessments, detect problems of a normative or nature from historical events and phenomena related to this issue. In addition, the author also uses other research methods such as analysis, synthesis, systematics, statistics, comparison, etc., in the process of processing materials as well as studying the contents inside each specific issue. The article was completed on the basis of exploiting resources at the Romanian National Archives, the Willson Center Online Archive (USA), as well as the research results of other authors. From there, the following will be clarified: First, The establishment of Romanian-Vietnamese relations and the importance of the Vietnamese people's resistance war against the US; Second, Romania's diplomatic efforts with socialist nations; Third, Assessments on Romania's diplomatic efforts towards communist nations. The results will clarify Romania's efforts to find a solution to end the war in Vietnam. At the same time, it will further clarify the support of socialist countries for Vietnam's resistance war against the US.